2014
DOI: 10.1177/0363546514531732
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Testing Environment and Baseline Performance in Child and Adolescent Concussion Assessment

Abstract: In this sample, children given a baseline assessment in a group setting performed no differently than children tested individually when standardized administration procedures were used by trained test administrators. Previous evidence suggesting differences between settings may be attributable to the variability in test administration and supervision rather than the environment itself. The importance of standardized procedures and proper supervision during baseline concussion assessment is supported by these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…18 The ImPACT battery also can be administered in a group setting without decreasing the validity of each composite score. 19 Overall, due to ImPACT's validity, convenience of administration, and heightened popularity among high schools, it was the ideal neuropsychological battery to examine.…”
Section: Neuropsychological Battery: Impactmentioning
confidence: 99%
“…18 The ImPACT battery also can be administered in a group setting without decreasing the validity of each composite score. 19 Overall, due to ImPACT's validity, convenience of administration, and heightened popularity among high schools, it was the ideal neuropsychological battery to examine.…”
Section: Neuropsychological Battery: Impactmentioning
confidence: 99%
“…In contrast, Vaughan, Gerst, Sady, Newman, & Gioia (2014) found that when test administrators were trained in neuropsychological testing and the test administration was standardized, there was no difference between scores obtained in group versus individualized testing for a group of 5-18 years old participants.…”
Section: Standardized Administration and Environment In Testingmentioning
confidence: 85%
“…However, several limitations are noted. First, the majority of baseline testing was completed in groups larger than recently recommended (Lichtenstein et al, 2014;Moser et al, 2011Moser et al, , 2013Vaughn et al, 2014). Yet even with less than optimal environments for baseline administrations, the results were informative and indicate unnecessary redundancy of repeat testing in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes were tested in groups by athletic training staff in quiet computer labs within the Athletic Department complex, or in the Center for Brain, Biology and Behavior assessment lab. There was variability in testing procedures, with the majority of testing completed in large groups with two to five supervisors and non-standardized instruction as is fairly typical (Vaughn et al, 2014). The original sample of baseline results from 2010 to 2014 included 899 records.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation